Random distribution pattern and non-adaptivity of genome size in a highly variable population of Festuca pallens - Smarda, Petr; Bures, Petr; Horová, Lucie (Annals of botany, 2007)
BACKGROUND AND AIMS: The spatial and statistical distribution of genome sizes and the adaptivity of genome size to some types of habitat, vegetation or microclimatic conditions were investigated in a tetraploid population of Festuca pallens. The population was previously documented to vary highly in genome size and is assumed as a model for the study of the initial stages of genome size differentiation. METHODS: Using DAPI flow cytometry, samples were measured repeatedly with diploid Festuca pallens as the internal standard. Altogether 172 plants from 57 plots (2.25 m(2)), distributed in contrasting habitats over the whole locality in South Moravia, Czech Republic, were sampled. The differences in DNA content were confirmed by the double peaks of simultaneously measured samples. KEY RESULTS: At maximum, a 1.115-fold difference in genome size was observed. The statistical distribution of genome sizes was found to be continuous and best fits the extreme (Gumbel) distribution with rare occurrences of extremely large genomes (positive-skewed), as it is similar for the log-normal distribution of the whole Angiosperms. Even plants from the same plot frequently varied considerably in genome size and the spatial distribution of genome sizes was generally random and unautocorrelated (P > 0.05). The observed spatial pattern and the overall lack of correlations of genome size with recognized vegetation types or microclimatic conditions indicate the absence of ecological adaptivity of genome size in the studied population. CONCLUSIONS: These experimental data on intraspecific genome size variability in Festuca pallens argue for the absence of natural selection and the selective non-significance of genome size in the initial stages of genome size differentiation, and corroborate the current hypothetical model of genome size evolution in Angiosperms (Bennetzen et al., 2005, Annals of Botany 95: 127-132).
Keywords: Genome, Plant; Adaptation, Biological; Festuca; molekulární evoluce; Evolution, Molecular; genetická variace; Geography; Genetic Variation; Models, Genetic; biologická adaptace; zeměpis; genom rostlinný; modely genetické; selekce (genetika); Selection, Genetic; ekosystém; Ecosystem